CORPORATE TAXATION, INVESTMENT DECISIONS AND ECONOMIC GROWTH: A STUDY OF SELECTED MANUFACTURING COMPANIES IN NIGERIA - ABDULSALAM S. ADEMOLA (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, ECONOMICS & MANAGEMENT, 2013)
This study examines the effect of corporate taxation on investment decision of manufacturing companies in Nigeria. It also establishes the relationship between tax revenue and economic growth, in order to determine the effects of rates, double and multiplicity of taxes on corporate income as well as the impact of tax revenue on economic growth. The study basically makes use of secondary data. Stratified sampling method was used to ensure proper grouping of the companies while Correlation and Regression analysis were employed to analyze data. The study established that there are cases of double and multiplicity of taxes levied by all the tiers of government. It was also found that, tax revenue has insignificant impact on economic growth. Therefore, government should create conducive and friendly business environment by a way of reducing the rate and numbers of taxes levied on the corporate organization’s income to encourage investment. Government should also provide necessary infrastructural facilities to reduce the cost of doing business. Nigerian government should encourage tax compliance and self assessment in order to increase revenue from taxes and achieve sustainable economic growth.